A short note on the rationality of the false consensus effect - Christoph Vanberg (University of Heidelberg, Department of Economics, 2019)
In experiments which measure subjects' beliefs, both beliefs about others' behavior and beliefs about others' beliefs, are often correlated with a subject's own choices. Such phenomena have been interpreted as evidence of a causal relationship between beliefs and behavior. An alternative explanation attributes them to what psychologists refer to as a "false consensus effect." It is my impression that the latter explanation is often prematurely dismissed because it is thought to be based on an implausible psychological bias. The goal of this note is to show that the false consensus effect does not rely on such a bias. I demonstrate that rational belief formation implies a correlation of behavior and beliefs of all orders whenever behaviorally relevant traits are drawn from an unknown common distribution. Thus, if we assume that subjects rationally update beliefs, correlations of beliefs and behavior cannot support a causal relationship.
urn:nbn:de:bsz:16-heidok-264097
Keywords: 330; Beliefs; behavioral economics; experimental economics